Methods of Attracting Foreign Investments to the National Economy - Zikirullaeva, Nilufar Dilmurod qizi (RA Journal of Applied Research, 2021)
The implementation of innovative processes at the modern level and the dynamic development of the national economy on this basis today are impossible without the intensive attraction of foreign investment. The volume of foreign investment is one of the indicators characterizing the degree of integration of the country into the world community and depends on the attractiveness of the investment object. The following article is devoted to the ways of attracting foreign investment in the national economy.